Thinking beyond sepsis to unmask a metabolic mystery: a rare case of neonatal maple syrup urine disease - Raut, Dinkar; Walhekar, Sagar Yamnaji; Misra, Anjini; Singh, Rachna (International Journal of Contemporary Pediatrics, 2025)
Maple syrup urine disease (MSUD) was first reported by paediatrician Menkes in 1954, as the α-ketoacid excreted in urine smells like maple syrup. MSUD is a rare genetic disorder which manifested as impaired branched-chain amino acid (BCAA) metabolism caused by branched-chain α-ketoacid dehydrogenase (BCKD) complex deficiency. Early diagnosis and treatment of MSUD is important for better outcomes. Feed intolerance, history of consanguinity between parents and that peculiar odour of maple syrup in urine should raise suspicion of the above. Timely referral, especially by clinicians practising in rural areas, is essential for early diagnosis and treatment. We present a case of MSUD with poor prognosis probably due to advanced disease at the time of presentation. The case highlights the importance of suspicion and early diagnosis of MSUD, as well as thinking beyond sepsis as the root of all problems.